Catalytic C–H Activation of Arylacetylenes: A Fast Assembly of 3-(Arylethynyl)-3-hydroxyindolin-2-ones Using CuI/DBU - Chouhan, Mangilal; Senwar, Kishna Ram; Kumar, Kapil; Sharma, Ratnesh; Nair, Vipin A. (Synthesis, 2014)
A highly efficient and atom-economic methodology has been developed for the synthesis of 3-(arylethynyl)-3-hydroxyindolin-2-ones from isatins by C–H activation of arylacetylenes using a catalytic quantity of copper(I) iodide (5 mol%) and DBU (20 mol%) at 25 °C, affording the products in excellent yields in very short reaction time (5 min).
Keywords: catalysis; C–H activation; copper(I) iodide; arylalkyne addition; 3-hydroxyindolin-2-ones